Lubuk Bauk mosque in Batipuh Baruh Country, a minangkabau traditional architectural perspective / Zusneli Zubir - Zubir, Zusneli (2012)
Historically, since Islam enters into Minangkabau, Surau institutions has been coloring the process of Islamization. Not only as a center of worship, the mosque becomes the next development of a community center and educational center. Some relics of the mosque and surau traditional Minangkabau characterized each of their own. Even AA Navis in his works, ensuring traditional mosque with typical houses belonging to gonjong kelarasan of Koto Piliang principle while the roof of a mosque has to do with the typical terraced property of Caniago Bodi principle. Does A.A Navis can be justified? Bauk Lubuk surau located in the lowland of Batipuh County, Tanah Datar regency, West Sumatra is one interesting case for discussion. Of architecture, this mosque is unique, even a few visitors from the West express admiration for the building. Bauk Lubuk surau built on donated land or waqf land given by Datuk Bandaro Panjang who comes from a tribe of Jambak, Jurai Nan Ampek tribe. Built by Batipuh lowland villagers under the coordination of eleders or the ninik mamak in 1896 and completed in 1901. Surau Lubuk Bauk consists of three floors which have different meanings in deciding the case at the level of village. Its architecture is disclaimed as a characteristic of the Koto Piliang. Traditional mosque symbolizes the four tribes in Batipuah Baruah County, the tribe Koto, Piliang, Tanjuang and Jambak. How does the history of the Surau Lubuk Bauk? Is this true symbol of concord between Koto and Piliang? How complex is the architecture of Surau Lubuk Bauk?